Short-term fasting before living kidney donation has an immune-modulatory effect - Oudmaijer, Christiaan A. J.; Komninos, Daphne S. J.; Ozinga, Rutger A.; Smit, Kimberly; Rozendaal, Nina E. M.; Hoeijmakers, Jan H. J.; Vermeij, Wilbert P.; Aerts, Joachim G. J. V.; IJzermans, Jan N. M.; Willemsen, Marcella (Frontiers in Immunology, 2025)
BackgroundShort-Term Fasting (STF) is an intervention reducing the intake of calories, without causing undernutrition or micronutrient-related malnutrition. It aims to systemically improve resilience against acute stress. Several (pre-)clinical studies have suggested protective effects of STF, marking the systemic effects STF can induce in respect to surgery and ischemia-reperfusion injury. In addition, STF also affects the number of circulating immune cells. We aim to determine the effect of STF on the abundance and phenotype of different immune cell populations.MethodsThirty participants were randomly selected from the FAST clinical trial, including living kidney donors, randomized to an STF-diet or control arm. In an observational cohort sub-study we prospectively included 30 patients who donated blood samples repeatedly during study runtime. Using flow cytometry analyses, immune cell phenotyping was performed on peripheral blood mononuclear cells. Three panels were designed to investigate the presence and activation status of peripheral T cells, B cells, dendritic cells (DCs) and myeloid cells.ResultsEight participants were excluded due to sample constraints. Baseline characteristics showed no significant differences, except for fasting duration. Weight changes were minimal and non-significant across different time intervals, with slight trends toward long-term weight loss pre-surgery. Glucose, insulin, and β-hydroxybutyrate levels differed significantly between groups, reflecting adherence to the fasting diet. Flow cytometry and RNA sequencing analysis revealed no baseline differences between groups, with high variability within each group. STF changes the levels and phenotype of immune cells, reducing the abundance and activation of T cells, including regulatory T cells, increased presence of (naïve) B cells, and elevation of type 1 conventional DCs (cDC1s). In addition, a decrease in central memory T cells was observed.DiscussionIn this study, we observed significant changes due to fasting in B cells, T cells, and DCs, specifically toward less specialized lymphocytes, suggesting an arrest in B and T cell development. Further research should focus on the clinical implications of changes in immune cells and significance of these observed immunological changes.ConclusionSTF results in reduced numbers and activation status of T cells and Tregs, increased presence of (naïve) B cells, and elevation of cDC1s.